Evidence-based orthodontics: Appraisal of the methodologies of systematic reviews and meta-analyses in controversial areas of orthodontics - ACAR, ZEYNEP AHÜ (My University, 2013)
Background: This article aimed to evaluate the methodologic quality of systematic reviews (SRs) and meta-analyses (MAs) related to three controversial areas of orthodontics. Methods: Electronic database searches of published orthodontic literature (SRs and MAs) were performed. Three research questions were formulated to include articles in the study: 1) What is the interrelation between orthodontic treatment and temporomandibular disorders (TMDs)?; 2) What is the effect of functional treatment on mandibular growth?; and 3) What differences can be found in a comparison of early/two-phase and late/one-phase orthodontic treatment for Class II malocclusion in growing patients? Studies satisfying the inclusion criteria were appraised in terms of their methodology. The tool for the assessment of the methodology used was the Revised-Assessment of Multiple Systematic Reviews (R-AMSTAR). Results: A search revealed 10 studies that satisfied our inclusion criteria. R-AMSTAR evaluations ranged between 13 and 44 points (mean ± SD 29.7 ± 9.44). Three SRs were classified as high-quality studies, two of good quality, and five were judged as having fair to low quality methodology. Further analysis of the results was performed and presented in accordance with the conclusions of each study. Conclusions: R-AMSTAR is a readily applicable and validated tool for assessing the methodology of a SR. Most of the SRs concerning our research questions were of average quality. Efforts should be made to reduce methodologic flaws. © 2013 World Federation of Orthodontists.
Keywords: Evidence-based orthodontics; Meta-analysis; R-AMSTAR; Systematic review